Four Parameters for Measuring Democratic Deliberation: Theoretical and Methodological Challenges and How to Respond - Dannica Fleuß; Karoline Helbig; Gary S. Schaal (Politics and Governance, 2018)
Although measuring democratic deliberation is necessary for a valid measurement of the performance of democracies, it poses serious theoretical and methodological challenges. The most serious problem in the context of research on democratic performance is the need for a theoretical and methodological approach for “upscaling” the measurement of deliberation from the micro and meso level to the macro level. The systemic approach offers a useful framework for this purpose. Building on this framework, this article offers a modular approach consisting of four parameters for conceptualization, measurement, and aggregation which can be adjusted to make the measurement of democratic deliberation compatible with the various general measurement approaches adopted by different scholars.